Prenatal serum screening for Down syndrome and neural tube defects in the United States: Changes in utilization patterns from 2012 to 2020. (December 2021) - Lepage, Nathalie; Wyatt, Philip; Ashwood, Edward R; Best, Robert G; Long, Thomas; Palomaki, Glenn E
Objective: To compile current usage of serum-based prenatal screening for Down syndrome in the United States and compare it with results from a similar 2011/2012 survey. Setting: The College of American Pathologists maternal screening proficiency testing survey includes a supplemental question on the first of three yearly distributions. Methods: Information regarding tests offered and the monthly number of pregnancies tested for US-based laboratories were reviewed. Results were stratified by size of laboratory, tests offered, and pregnancies tested. Findings were compared to an earlier survey. Results: Fifty-six laboratories reported they will have screened 1, 131, 336 pregnancies in 2020. Of these, 36% are screened by stand-alone first trimester testing, 48% by stand-alone second trimester testing, and 16% using tests that integrate results from both trimesters. Eighty percent of all serum screens were provided by the five laboratories that performed the most screens (at least 50, 000). These five performed similar proportions of first or second trimester screens (42.2% and 41.8%, respectively). Compared to eight years earlier, there are now 54% fewer laboratories. Pregnancies screened using the first trimester, second trimester, and integrated protocols were lower by 27%, 69%, and 72%, respectively. The serum screening activity in the US showed a 62% decrease from 2012 levels. During 2012–2020, the number of cell-free DNA tests increased from negligible to 1, 492, 332. Conclusions: Maternal serum screening for common aneuploidies has changed significantly in eight years with fewer laboratories, a shift toward larger laboratories and a 2.5-fold reduction in pregnancies tested, likely due to the introduction of cell-free DNA screening.